Cathode materials and batteries
By designing a secondary particle structure composed of multiple primary particles in the positive electrode material and controlling its size and porosity, the problem of poor thermal stability and cyclic stability when increasing capacity is solved, and higher structural stability and lithium ion diffusion performance are achieved.
Patent Information
- Application Number
- CN202411976391.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
AI Technical Summary
While the existing cathode materials increase their capacity, the thermal stability is reduced and the long cycle stability is difficult to maintain, resulting in poor structural stability and lithium ion diffusion performance.
Using a secondary particle structure composed of multiple primary particles, the SEM sectional image of the secondary particles is observed through scanning electron microscope, and the number of primary particles with a radial size ≥1μm is controlled to be between 50% and 70%, and the proportion of the appropriate pore area is between 17% and 23%, to optimize the structure of the positive electrode material.
The structural stability and lithium ion diffusion performance of the positive electrode material are improved, the rate performance and cycling performance are enhanced, and the battery gas production phenomenon and insufficient mechanical strength are reduced.
Smart Images

Figure CN119786567A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of positive electrode materials, and in particular relates to positive electrode materials and batteries. Background Art
[0002] Lithium-ion batteries are widely used in laptops, mobile phones, digital products and other fields due to their high energy density, good safety performance, long cycle life and environmental friendliness. The development of positive electrode materials is relatively slow compared to the development of large-capacity negative electrode materials (about 800-1000mAh / g). Therefore, researchers currently focus on developing large-capacity and high-voltage positive electrode materials to improve the energy density of lithium-ion batteries.
[0003] As the capacity of the positive electrode material increases, it will inevitably cause problems such as reduced thermal stability and difficulty in maintaining long-cycle stability. Therefore, how to improve the structural stability of the positive electrode material, improve the lithium ion diffusion performance, and improve the rate performance and cycle performance of the positive electrode material is one of the problems that need to be solved urgently. Summary of the invention
[0004] The present application provides a positive electrode material and a battery. The positive electrode material of the present application has excellent structural stability, can improve the lithium ion diffusion performance, and improve the rate performance and cycle performance of the positive electrode material.
[0005] In a first aspect, the present application provides a positive electrode material, the positive electrode material comprising secondary particles, the secondary particles comprising a plurality of primary particles;
[0006] The SEM cross-sectional image of the secondary particles was measured by a scanning electron microscope at a magnification of 5K. In the SEM cross-sectional image of the secondary particles, the average number of primary particles with a radial size ≥1 μm accounted for L%, the average area of the pores accounted for P%, 50≤L≤70, 17≤P≤23.
[0007] In some embodiments, 0.3≤P / L≤0.4.
[0008] In some embodiments, in the SEM cross-sectional image of the positive electrode material secondary particles, the number of primary particles with a radial size ≥1 μm is n1, and the total number of primary particles is n0, wherein 130≤n0≤190, 70≤n1≤120.
[0009] In some embodiments, the average particle size of the primary particles is 0.5 μm to 4 μm.
[0010] In some embodiments, the chemical formula of the positive electrode material is Li n Ni x Co y M z Te O2, wherein 0.95≤n≤1.6, 0.8≤x<1, 0<y+z≤0.2, x+y+z+e=1, 0≤e≤0.003, wherein M is Mn and / or Al, and T element is a metal element and / or a non-metal element.
[0011] In some embodiments, the T element includes at least one of Al, Mg, Sr, Ca, Ti, La, W, Nb, Y, Gd, B, P, and N.
[0012] In some embodiments, the mass percentage of the T element in the positive electrode material is 0 to 3000 ppm.
[0013] In some embodiments, the positive electrode material is measured by XRD ray, and the half-peak width of the 003 diffraction peak of the positive electrode material is 0.127-0.174, and the peak intensity ratio of the 003 diffraction peak to the 104 diffraction peak of the positive electrode material is 1. 003 / I 104 It is 1.6 to 1.8.
[0014] In some embodiments, the positive electrode material further includes a coating located on at least a portion of the surface of the secondary particles, wherein the coating is Li m T a O b , 0≤m<0.5,0 <a<0.002,0<b≤2。
[0015] In some embodiments, the specific surface area of the positive electrode material is 0.32 m 2 / g~0.74m 2 / g.
[0016] In some embodiments, the tap density of the positive electrode material is 2.2 g / cm 3 ~2.9g / cm 3 .
[0017] In some embodiments, the volume distribution median particle size D50 of the positive electrode material is 8 μm to 13 μm.
[0018] In some embodiments, the powder conductivity of the positive electrode material under a pressure of 20 MPa is 0.002 S / cm to 0.03 S / cm.
[0019] In some embodiments, the lithium ion diffusion rate of the positive electrode material is D cm 2 / s, 10 -12 ≤D≤10 -8 .
[0020] In some embodiments, the oil absorption value of the positive electrode material is Q mL / 100g, and 12≤Q≤18.
[0021] In some embodiments, the mass percentage of residual alkali on the surface of the positive electrode material is 0.04 wt % to 0.16 wt %.
[0022] In a second aspect, the present application provides a battery, comprising a positive electrode material.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] In the present application, the positive electrode material includes secondary particles, the secondary particles include a plurality of primary particles, the primary particles include nano-scale primary particles with a relatively small radial size (<1 μm) and micro-scale primary particles with a relatively large radial size (≥1 μm), wherein the micro-scale primary particles have better structural stability, and the stress generated during the cycle can be better released in the radial direction of the secondary particles through the micro-scale primary particles, which is conducive to maintaining the structural stability of the secondary particles and improving the safety of the positive electrode material. The size of the nano-scale primary particles is relatively small, and the transmission efficiency of lithium ions between the nano-scale primary particles is higher, which is conducive to improving the rate performance of the positive electrode material during the charge and discharge process; however, too many nano-scale primary particles will increase the number of grain boundaries in the secondary particles, resulting in an increase in the impedance of the positive electrode material, which is not conducive to the performance of the rate performance and cycle performance of the positive electrode material. Therefore, the present application controls the proportion of the number of primary particles with a radial size ≥1 μm in the secondary particles of the positive electrode material to L between 50% and 70%, and the cooperation of the nano-scale primary particles and the micro-scale primary particles can improve the structural stability of the secondary particles while improving the lithium ion diffusion efficiency. At the same time, the pore area ratio P in the secondary particles is collaboratively controlled to be between 17% and 23%, so that the positive electrode material has a higher mechanical strength, reduces the particle breakage of the secondary particles during the pole piece rolling process, reduces the side reaction between the positive electrode material and the electrolyte, and thus reduces the gas production of the battery prepared by the positive electrode material. At the same time, an appropriate amount of pores can also provide more lithium ion transmission channels, reduce the transmission distance of lithium ions, and improve the efficiency of lithium ion transmission. Therefore, the present application collaboratively controls the P value of the positive electrode material and the number of micron-sized primary particles L to be between 50% and 70%, and the positive electrode material has excellent structural stability, which can improve the lithium ion diffusion performance, and improve the rate performance and cycle performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the embodiments of the present application or the technical solutions of the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0026] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application.
[0027] Figure 2 This is a cross-sectional SEM image of the positive electrode material prepared in Example 1 of the present application.
[0028] Figure 3 This is a diagram showing the size and number of primary particles in the cross-sectional SEM image of the positive electrode material prepared in Example 1 of the present application.
[0029] Figure 4 This is a graph of the porosity area ratio in the cross-sectional SEM image of the positive electrode material prepared in Example 1 of the present application. DETAILED DESCRIPTION
[0030] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0031] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0032] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0033] In order to easily understand the present invention, specific terms are appropriately defined in this application. Unless otherwise defined herein, scientific terms and technical terms used in the present invention have the meanings commonly understood by those skilled in the art to which the present invention belongs.
[0034] As used herein, the term "primary particles" refers to particles that exist individually without forming agglomerates.
[0035] As used herein, the term "secondary particles" refers to particles formed by agglomeration of the above-mentioned primary particles.
[0036] The present application provides a positive electrode material, which includes secondary particles, and the secondary particles include multiple primary particles; a SEM cross-sectional image of the secondary particles is measured by a scanning electron microscope at a magnification of 5K. In the SEM cross-sectional image of the secondary particles, the number of primary particles with a radial size ≥1 μm accounts for L·%, the area of pores accounts for P%, 50≤L≤70, 17≤P≤23.
[0037] In the present application, the positive electrode material includes secondary particles, and the secondary particles include multiple primary particles; the primary particles include nano-scale primary particles with a smaller radial size (<1μm) and micron-scale primary particles with a larger radial size (≥1μm), wherein an appropriate amount of micron-scale primary particles enables the stress generated by the positive electrode material during the cycle to be better released in the radial direction of the secondary particles through the micron-scale primary particles, which is beneficial to maintain the structural stability of the secondary particles and improve the safety of the positive electrode material. The size of the nano-scale primary particles is smaller, and the transmission efficiency of lithium ions between the nano-scale primary particles is higher, which is beneficial to improve the rate performance of the positive electrode material during the charge and discharge process. Therefore, the present application controls the number of primary particles with a radial size ≥1μm in the secondary particles of the positive electrode material to account for L between 50% and 70%. Under the coordinated effect of the nano-scale primary particles and the micron-scale primary particles, the lithium ion diffusion efficiency can be improved while improving the structural stability of the secondary particles. At the same time, the pore area ratio P in the secondary particles is coordinated to be controlled between 17% and 23%, so that the positive electrode material has a higher mechanical strength, which can reduce the particle breakage of the secondary particles during the rolling process of the pole piece, reduce the side reaction between the positive electrode material and the electrolyte, and thus reduce the gas production of the battery prepared by the positive electrode material. The right amount of pores can also provide more lithium ion transmission channels, reduce the transmission distance of lithium ions, and provide lithium ion transmission efficiency. Therefore, the present application controls the value of P of the positive electrode material to be between 17 and 23 and the number of micron-sized primary particles to account for L between 50% and 70%. The positive electrode material has excellent structural stability, which can improve the lithium ion diffusion performance, and improve the rate performance and cycle performance of the positive electrode material. It should be noted that the primary particles in this application are in the shape of long strips, and the radial size of the primary particles in this application refers to the longest diameter of the primary particles.
[0038] In some embodiments, L can be 50, 55, 56, 58, 60, 62, 65, 68, 70 or any value within the above range, which is not limited here. When the number of micron-sized primary particles in the secondary particles of the positive electrode material accounts for 50%-70%, an appropriate amount of micron-sized primary particles can make the stress generated by the positive electrode material during the cycle be well released in the radial direction of the secondary particles, which is beneficial to improve the structural stability of the secondary particles and improve the safety performance of the positive electrode material. At the same time, since 50≤L≤70, the number of nano-sized primary particles with a radial size of less than 1μm accounts for 30%-50%. Since the size of nano-sized primary particles is small, it is beneficial to improve the diffusion rate of lithium ions in the positive electrode material during the charge and discharge process, and comprehensively improve the rate performance and cycle performance of the positive electrode material. Under the synergistic effect of an appropriate amount of micron-sized primary particles and nano-sized and primary particles, the rate, cycle and safety performance of the positive electrode material can be well improved.
[0039] When L is less than 50%, the number of nanometer-sized primary particles at the cross section of the positive electrode material increases, the number of grain boundaries between the primary particles increases, the impedance increases, and the lithium ion diffusion efficiency of the positive electrode material decreases, thereby affecting the rate and cycle performance of the positive electrode material; at the same time, the proportion of micrometer-sized primary particles decreases, resulting in the stress of the secondary particles not being fully released during the cycle. After a long cycle, microcracks are prone to appear in the secondary particles, resulting in the intensification of the side reaction between the secondary particles and the electrolyte, affecting the cycle performance and safety performance of the positive electrode material. When L is greater than 70%, the proportion of micrometer-sized primary particles increases, which will improve the cycle stress resistance of the positive electrode material, but due to the longer radial size of the micrometer-sized primary particles, the lithium ion transmission path becomes longer, the lithium ion diffusion rate decreases, and the rate performance of the positive electrode material is affected; at the same time, the proportion of nanometer-sized primary particles decreases, which further reduces the number of lithium ion diffusion in the positive electrode material. Under the combined effect of the two, the rate performance and cycle performance of the positive electrode material are reduced.
[0040] In some embodiments, in the SEM cross-sectional image of the secondary particles, the area ratio of the pores is P%, 17≤P≤23, and the P% value can be specifically 17%, 18%, 19%, 20%, 21%, 22%, 23% or any value therebetween, which is not limited here. It can be understood that if the P value is too large, the mechanical strength of the positive electrode material will decrease, and the particles will easily break during the rolling process of the pole piece. It will also lead to the intensified reaction between the positive electrode material and the electrolyte, the capacity and first efficiency of the positive electrode material will decrease, and the particle stability of the positive electrode material will decrease. When the P value is too small, the lithium ion transmission channels in the positive electrode material particles are reduced, and the lithium ion transmission efficiency decreases. Therefore, the present application controls the P value within the above range, which is beneficial to improve the first coulomb efficiency and capacity of the positive electrode material while improving the lithium ion diffusion performance, and improving the rate performance and cycle performance of the positive electrode material.
[0041] In some embodiments, the positive electrode material satisfies 0.3≤P / L≤0.4, and the specific value of P / L can be 0.301, 0.31, 0.32, 0.33, 0.34, 0.35, 0.36, 0.38, 0.398 or any value within the above range, which is not limited here. When 0.4<P / L, on the one hand, the porosity P in the secondary particles of the positive electrode material is large, the density of the positive electrode material will be reduced, the tap density and mechanical strength of the positive electrode material will be reduced, and the electrolyte is easy to pass through a large number of pores to cause side reactions inside the secondary particles, so that the structure of the positive electrode material is further destroyed, and the cycle performance and safety performance of the positive electrode material are reduced. On the other hand, the number of micron-sized primary particles accounts for a small proportion L, and the stress generated during the long cycle of the positive electrode material is difficult to be released. Microcracks are prone to appear inside the secondary particles. During the cycle, the secondary particle structure is destroyed, especially under the dual influence of the increase in pores, the cycle stability of the positive electrode material is further reduced. When 0.3>P / L, on the one hand, the porosity P in the secondary particles of the positive electrode material is small, the density of the positive electrode material is too high, the ion transmission channels are reduced, the lithium ion diffusion rate will be greatly reduced, the instantaneous discharge rate of the positive electrode material will decrease, and the interface impedance of the positive electrode material will increase; on the other hand, the proportion of micron-sized primary particles will increase, which will further increase the lithium ion transmission path of the positive electrode material. During the lithium ion transmission process, the positive electrode material will consume more electricity and generate more heat. After a long cycle, the positive electrode material is prone to thermal runaway, thereby affecting the safety performance of the positive electrode material. This application controls the range of 0.3≤P / L≤0.4, which is conducive to the positive electrode material having both excellent cycle performance and rate performance, and improving the structural stability of the positive electrode material.
[0042] In some embodiments, the chemical formula of the positive electrode material is: Li n Ni x Co y M z T e O2, wherein 0.95≤n≤1.6, 0.8≤x<1, 0<y+z≤0.2, x+y+z+e=1, 0≤e≤0.003, wherein M is Mn and / or Al, and T is a metal or non-metal element.
[0043] Specifically, the value of n can be 0.95, 0.98, 0.99, 1.01, 1.05, 1.1, 1.2, 1.3, 1.4, 1.5 or 1.6, the value of x can be 0.8, 0.82, 0.85, 0.88, 0.90, 0.92, 0.95 or 0.99, the value of y+z can be 0.01, 0.05, 0.08, 0.09, 0.10, 0.15, 0.18 or 0.2, and the value of e can be 0, 0.001, 0.002, 0.003 or any value within the above range, which is not limited here.
[0044] It should be noted that the content of each element in the positive electrode material can be measured by a known instrument for qualitative analysis and / or quantitative analysis of each element, such as ICP and ICP-MS.
[0045] In some embodiments, the T element includes at least one of Al, Mg, Sr, Ca, Ti, La, W, Nb, Y, Gd, B, P, and N.
[0046] In some embodiments, the mass percentage of the T element in the positive electrode material is 0 to 3000 ppm, specifically 0, 10 ppm, 50 ppm, 80 ppm, 100 ppm, 200 ppm, 300 ppm, 500 ppm, 700 ppm, 1000 ppm, 2000 ppm, 3000 ppm or any value therebetween, which is not limited here. The mass percentage of the T element in the positive electrode material is controlled within the above range, which can change the lattice constant of the positive electrode material or the valence state of the transition element, reduce cation mixing, and improve the conductivity and structural stability of the positive electrode material, thereby improving the cycle performance of the positive electrode material.
[0047] In some embodiments, the positive electrode material includes secondary particles, and the secondary particles include a plurality of primary particles. Specifically, the secondary particles are spherical in structure, and the primary particles in the secondary particles are tightly combined to form secondary particles, which is beneficial to improve the gram capacity of the positive electrode material.
[0048] In some embodiments, the pores in the secondary particles extend radially. During the charge and discharge process of the positive electrode material, the elongated pores enable the primary particles in the positive electrode material particles to be arranged radially to fully contact with the electrolyte immersed in the pores, shortening the lithium ion transmission path, accelerating the transmission of lithium ions, and improving the first discharge capacity and the first coulomb efficiency. The radially extending pores are conducive to the full release of the accumulated stress caused by the lattice phase change, which can improve the structural stability of the positive electrode material particles, reduce particle breakage, and thereby reduce the loss of active ions due to the continuously formed broken surfaces, and reduce the irreversible loss of capacity. In the SEM radial cross-section of the secondary particles, the primary particles are arranged radially along the secondary particles, the primary particles are in the shape of long strips, and the radial dimension of the primary particles is the longest diameter of the primary particles.
[0049] In some embodiments, in the SEM cross-sectional image of the secondary particles of the positive electrode material, the number of primary particles with a particle size ≥1 μm is n1, the total number of primary particles is n0, and the proportion of primary particles with a particle size ≥1 μm in all particles is L = n1 / n0%, 50≤L≤70, and L can specifically be 50%, 55%, 58%, 60%, 62%, 65%, 68%, 70% or any value therebetween, which is not limited here.
[0050] In some embodiments, 130≤n0≤190, and the total number of primary particles n0 can specifically be 130, 140, 150, 160, 170, 180, 190 or any value therebetween, which is not limited herein.
[0051] In some embodiments, 70≤n1≤120, the number n1 of primary particles with a particle size ≥1 μm can specifically be 70, 80, 90, 100, 110, 120 or any value therebetween, which is not limited herein.
[0052] In some embodiments, the particle size of the primary particles is 0.5 μm to 4 μm, and specifically can be 0.5 μm, 0.8 μm, 1 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm or any value therebetween, which is not limited here. It should be noted that the particle size of the primary particles refers to the length dimension of the primary particles along the radial direction of the secondary particles.
[0053] In some embodiments, the positive electrode material further includes a coating located on at least a portion of the surface of the secondary particles, and the coating is located on the surface of the secondary particles and the surface of the primary particles located in the surface region of the secondary particles.
[0054] In some embodiments, the chemical formula of the coating is Li m T n O o, 0≤m<0.5, 0≤n<0.002, 0≤o≤2. It can be understood that the T element participates in forming a lithium metal oxide coating layer coated on the particle surface. On the one hand, the generated lithium metal oxide acts as a protective layer to improve the structural stability of the positive electrode material. On the other hand, the lithium metal oxide has conductivity and can reduce the impedance of the positive electrode material.
[0055] In some embodiments, the cathode material is measured by XRD ray, and the half-peak width of the 003 diffraction peak of the cathode material is 0.127-0.174, 0.127, 0.130, 0.140, 0.150, 0.155, 0.160, 0.164, 0.170, 0.174 or any value therebetween, which is not limited here. The atoms / ions in the cathode material of the present application are arranged more orderly, the layered structure is more stable, and the thermal stability and cycle performance are excellent.
[0056] In some embodiments, the positive electrode material is measured by XRD ray, and the peak intensity ratio of the 003 diffraction peak and the 104 diffraction peak of the positive electrode material is 003 / I 104 The positive electrode material I is 1.6 to 1.8, and specifically can be 1.6, 1.62, 1.65, 1.68, 1.7, 1.73, 1.75, 1.8 or any value therebetween. 003 / I 104 When the ratio is within the above range, it means that the crystal structure of the positive electrode material is more ordered and stable. During the charge and discharge process, lithium ions can be more stably and smoothly deintercalated, which can reduce the lattice distortion of the positive electrode material and improve the cycle stability of the positive electrode material.
[0057] In some embodiments, the volume distribution median particle size D50 of the positive electrode material is 8 μm to 13 μm, specifically 8 μm, 9 μm, 10 μm, 11 μm, 12 μm or 13 μm, etc., and of course, it can be other values within the above range, which is not limited here. Controlling the particle size of the positive electrode material within the above range is conducive to improving the rate performance and cycle stability of the positive electrode material.
[0058] In some embodiments, the specific surface area of the positive electrode material is 0.32 m 2 / g~0.74m 2 / g, specifically 0.32m 2 / g, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g or 0.74m 2 / g, etc., and of course, it can also be other values within the above range, which is not limited here. Controlling the specific surface area of the positive electrode material within the above range is beneficial to improving the rate performance and cycle stability of the positive electrode material.
[0059] In some embodiments, the tap density of the positive electrode material is 2.2 cm 3 / g~2.7cm 3 / g, specifically 2.2cm 3 / g, 2.3cm 3 / g, 2.4cm 3 / g, 2.5cm 3 / g, 2.6cm 3 / g or 2.7cm 3 / g, etc., and of course, it can also be other values within the above range, which is not limited here. Controlling the tap density of the positive electrode material within the above range is beneficial to improving the energy density of the positive electrode material.
[0060] In some embodiments, the oil absorption value of the positive electrode material is Q mL / 100g, 12≤Q≤18; the oil absorption value Q of the positive electrode material can be specifically 12mL / 100g, 13mL / 100g, 14mL / 100g, 15mL / 100g, 16mL / 100g, 17mL / 100g or 18mL / 100g, etc., and of course it can also be other values within the above range, which are not limited here. The oil absorption value of the positive electrode material is related to the pore ratio of the positive electrode material. In the process of preparing the positive electrode slurry, if the oil absorption value of the positive electrode material is too high, it will lead to an increase in the consumption of the dispersant and binder required for preparing the slurry, that is, the mass ratio of the positive electrode material in the positive electrode slurry decreases, reducing the battery energy density and increasing the processing cost; when the oil absorption value of the positive electrode material is too low, the dispersibility of the positive electrode material in the positive electrode slurry decreases. In the present application, without affecting the processing performance and processing cost of the positive electrode material, the oil absorption value of the positive electrode material is controlled within the above range, which is beneficial to improving the compatibility of the positive electrode material with the electrolyte. The positive electrode material has better adsorption and wetting properties for the electrolyte, which can effectively reduce the interface resistance between the positive electrode material and the electrolyte, which is beneficial to improving the transmission of lithium ions and electrons, and making the electrochemical performance of the positive electrode material better.
[0061] In some embodiments, the powder conductivity of the positive electrode material under a pressure of 20 MPa is 0.002S / cm to 0.03S / cm, specifically 0.002S / cm, 0.004S / cm, 0.006S / cm, 0.008S / cm, 0.01S / cm, 0.012S / cm, 0.015S / cm, 0.02S / cm, 0.025S / cm, 0.03S / cm or any value therebetween, which is not limited here.
[0062] In some embodiments, the lithium ion diffusion rate of the positive electrode material is D cm 2 / s, 10 -12 ≤D≤10 -8 , which can be 10 -12 cm 2 / s, 10 -11 cm 2 / s, 10 -10 cm 2 / s, 10 -9 cm 2 / s, 10 -8 cm 2 / s or any value in between, without limitation.
[0063] In some embodiments, the mass percentage of residual alkali on the surface of the positive electrode material is 0.04wt% to 0.16wt%. Specifically, it can be 0.04wt%, 0.05wt%, 0.06wt%, 0.07wt%, 0.08wt%, 0.09wt%, 0.1wt%, 0.12wt%, 0.14wt%, 0.16wt% or any value therebetween, which is not limited here. The residual alkali on the surface of the positive electrode material mainly includes Li2CO3 and LiOH. Controlling the mass percentage of the residual alkali on the surface of the positive electrode material within the above range can reduce the corrosion effect of the residual alkali component on the coating layer, improve the structural stability and cycle stability of the positive electrode material, improve the processing performance of the positive electrode material and reduce the gas production of the battery prepared by the positive electrode material.
[0064] In a second aspect, the present application also proposes a method for preparing a positive electrode material, comprising the following steps:
[0065] S10, subjecting the first mixture including the cathode material precursor, the lithium source, the T element dopant and the pore former to a primary sintering treatment to obtain a primary sintering product; wherein the primary sintering treatment temperature is 700° C. to 770° C., and the time is 5 h to 13 h.
[0066] In some embodiments, the chemical formula of the positive electrode material precursor is Ni a1 Co b1 M c1 (OH)2 or Ni a1 Co b1 M c1 O2, wherein M is Mn and / or Al, and 0.8≤a1≤1, 0 <b1+c1≤0.2,a1+b1+c1=1。
[0067] In some embodiments, the lithium source includes at least one of hydrated lithium hydroxide, lithium hydroxide, lithium oxide, lithium carbonate, lithium acetate, lithium nitrate, and lithium oxalate.
[0068] In some embodiments, the molar ratio of metal Me in the positive electrode material precursor to Li in the lithium source is 1.01≤Li / Me≤1.05. Specifically, Li / Me can be 1.01, 1.02, 1.03, 1.04, 1.05, etc., where Me represents the molar content of all metals in the positive electrode material precursor. Controlling the Li / Me molar ratio within the above range is beneficial to the formation of primary particles of the positive electrode material and the improvement of the electrochemical properties of the positive electrode material.
[0069] In some embodiments, the T element includes at least one of Al, Mg, Sr, Ca, Ti, La, W, Nb, Y, Gd, B, P, and N.
[0070] In some embodiments, the dopant includes at least one of a salt of element T and an oxide of element T, such as ZrO2, TiO2, WO3, Nb2O5, CoOOH, Al2O3, Sb2O3, AlOOH, etc.
[0071] In some embodiments, the pore-forming agent Q is at least one of lithium sulfate, lithium antimonate, lithium silicate, lithium selenate, and lithium phosphate.
[0072] In some embodiments, the mass ratio of the positive electrode material precursor to the pore former is 1:(0.0005-0.002), specifically 1:0.0005, 1:0.0008, 1:0.0009, 1:0.001, 1:0.0015, 1:0.002 or any value therebetween. The present application controls the amount of the pore former added within the above range, and the lithium ions in the pore former will occupy more lithium positions, thereby increasing the porosity of the positive electrode material, and promoting the radial growth of the primary particles, thereby increasing the number of micron-sized particles.
[0073] In some embodiments, the mass ratio of the positive electrode material precursor to the dopant is 1:(0-0.003), specifically 1:0.0005, 1:0.0008, 1:0.0009, 1:0.001, 1:0.0015, 1:0.002, 1:0.0025, 1:0.003 or any value therebetween.
[0074] When the amount of dopant added to the first mixture is too much, it is not conducive to the growth of primary particles, so that the primary particles are not fully melted, resulting in an increase in the number of primary particles below 1 μm in the secondary particles. An appropriate amount of lithium salt in the first mixture can promote the melting of primary particles and the growth of primary particles, thereby increasing the proportion of primary particles above 1 μm.
[0075] In some embodiments, the primary sintering process is performed in an oxygen-containing atmosphere.
[0076] In some embodiments, the temperature of the primary sintering treatment is 700°C to 770°C, specifically 700°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C or any value therebetween.
[0077] In some embodiments, the sintering time is 5 h to 13 h; specifically, it can be 5 h, 8 h, 10 h, 12 h, 13 h or any value therebetween.
[0078] S20, performing a secondary sintering treatment on the primary sintered product and the second mixture of the T element dopant to obtain a secondary sintered product; wherein the secondary sintering treatment temperature is 500° C. to 700° C., and the time is 3 h to 7 h.
[0079] In some embodiments, the temperature of the secondary sintering process may be 500° C., 550° C., 600° C., 650° C., 700° C. or any value therebetween.
[0080] In some embodiments, the time of the secondary sintering treatment may be 3 h, 4 h, 5 h, 6 h, 7 h or any value therebetween.
[0081] In some embodiments, before the secondary sintering treatment, the preparation method further includes crushing and screening the primary sintering product so that the particle size D50 of the primary sintering product is 10 μm to 13 μm, specifically 10 μm, 11 μm, 12 μm, 13 μm or any value therebetween.
[0082] In some embodiments, after the secondary sintering process, the preparation method further comprises crushing and screening the secondary sintered product.
[0083] In some embodiments, taking the mass of the secondary sintered product as 100%, the mass percentage of the T element in the secondary sintered product is 0-3000ppm, specifically 0ppm, 20ppm, 50ppm, 100ppm, 500ppm, 1000ppm, 2000ppm, 2500ppm or 3000ppm, etc., and of course, it can also be other values within the above range, which is not limited here.
[0084] S30, washing and drying the secondary sintered product to obtain a dried product.
[0085] The present application performs a washing treatment on the secondary sintered product, which can wash away the residual lithium on the surface and inside of the secondary sintered product, increase the pore area ratio of the secondary particles, and reduce the mass percentage of residual alkali on the surface of the positive electrode material.
[0086] In some embodiments, the washing liquid of the washing treatment includes at least one of water, anhydrous ethanol, citric acid, and acetic acid.
[0087] In some embodiments, the washing treatment includes mixing the secondary sintered product with deionized water in a certain proportion, stirring, and filtering to obtain a filtered product.
[0088] In some embodiments, the mass ratio of the secondary sintered product to deionized water is (0.5-3):1, specifically 0.5:1, 0.6:1, 0.8:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1 or any value therebetween.
[0089] In some embodiments, the temperature of the deionized water is 10° C. to 30° C., specifically 10° C., 20° C., 30° C. or any value therebetween.
[0090] In some embodiments, the stirring speed is 20 r / min to 800 r / min, specifically 20 r / min, 50 r / min, 100 r / min, 200 r / min, 400 r / min, 600 r / min, 800 r / min or any value therebetween.
[0091] In some embodiments, the washing treatment time is 3 min to 10 min, specifically 3 min, 4 min, 5 min, 6 min, 8 min, 10 min or any value therebetween.
[0092] In some embodiments, the water content of the filter cake after pressure filtration is ≤ 0.5 wt %.
[0093] In some embodiments, after the filtration, the preparation method further comprises side blowing the filtration product, and the side blowing air pressure is ≥ 0.6 MPa, and specifically can be 0.6 MPa, 0.8 MPa, 1.0 MPa, 1.2 MPa or any value therebetween.
[0094] In some embodiments, the side blowing time is 20 min to 80 min.
[0095] In some embodiments, the drying temperature is 150° C. to 230° C., specifically 150° C., 200° C., 230° C., or any value therebetween. The drying time is 18 h to 26 h, specifically 18 h, 20 h, 21 h, 22 h, 23 h, 24 h, 26 h, or any value therebetween.
[0096] S40, sintering the dried product and the third mixture of the coating agent containing the T element three times to obtain a positive electrode material.
[0097] In some embodiments, based on the mass of the dry product as 100%, the added amount of the coating agent containing the T element is 0-3000ppm, specifically 0ppm, 20ppm, 50ppm, 100ppm, 500ppm, 1000ppm, 2000ppm, 2500ppm or 3000ppm, etc., and of course, it can also be other values within the above range, which is not limited here.
[0098] In some embodiments, the tertiary sintering process is performed in an oxygen-containing atmosphere.
[0099] In some embodiments, the temperature of the three sintering treatments is 200°C to 500°C, specifically 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C or any value therebetween.
[0100] In some embodiments, the duration of the three sintering treatments is 3 h to 7 h, specifically 3 h, 4 h, 5 h, 6 h, 7 h or any value therebetween.
[0101] In some embodiments, the heating rates of the primary sintering treatment, the secondary sintering treatment, and the tertiary sintering treatment are 1°C / min to 3°C / min, specifically 1°C / min, 2°C / min, 3°C / min, or any value therebetween.
[0102] In some embodiments, the oxygen-containing atmosphere during the sintering process includes at least one of air, nitrogen, oxygen, argon, and carbon dioxide.
[0103] In some embodiments, the mixing machine is any one of a coating machine, a high mixer, and a mixer.
[0104] In some embodiments, the sintering equipment is any one of a box furnace, a rotary kiln, and a roller kiln.
[0105] In some embodiments, the filter press equipment is any one of a horizontal filter press, a vertical filter press, and a small filter press.
[0106] In some embodiments, the drying machine is any one of a vacuum oven, a blast bellows, a box furnace, and a roller kiln.
[0107] In a third aspect, the present application provides a battery, the battery comprising the positive electrode material of the first aspect or the positive electrode material prepared according to the preparation method of the positive electrode material.
[0108] The battery provided in the present application may be a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), including a housing, an electrode assembly, and an electrolyte. The electrode assembly and the electrolyte are both located in the housing. The housing may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), such as a soft-pack battery.
[0109] In other embodiments, the secondary battery may also be a steel shell battery, an aluminum shell battery, etc.
[0110] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application, such as Figure 1 As shown, the battery includes a shell and an electrode assembly, the electrode assembly includes a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3, and the separator 3 is arranged between the positive electrode sheet 1 and the negative electrode sheet 2. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet 1, the separator 3 and the negative electrode sheet 2 in sequence.
[0111] In other embodiments, the electrode assembly may also be a winding structure, which is formed by stacking a positive electrode sheet, a separator, and a negative electrode sheet in sequence and then winding them.
[0112] In some embodiments, the positive electrode sheet 1 includes a positive electrode current collector 11 and a positive electrode active material layer 12 disposed on at least one surface of the positive electrode current collector 11 .
[0113] In some embodiments, the positive electrode current collector 11 may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil (aluminum foil or nickel foil, etc.) and a polymer substrate. The positive electrode active material layer 12 comprises a positive electrode active material, a conductive agent, and a binder, wherein the positive electrode active material is the positive electrode material of the first aspect described above or a positive electrode material prepared according to the preparation method of the positive electrode material described above.
[0114] In some embodiments, the negative electrode sheet 2 includes a negative electrode current collector 21 and a negative electrode active material layer 22 disposed on at least one surface of the negative electrode current collector.
[0115] In some embodiments, the negative electrode current collector 21 can be made of at least one of copper foil, nickel foil, stainless steel foil, titanium foil or a carbon-based current collector, or can be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.
[0116] In some embodiments, the negative electrode active material layer 22 includes a negative electrode material, and the negative electrode material includes but is not limited to artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material can be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material can be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.
[0117] The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium ion battery, a sodium ion battery, a solid electrolyte battery, etc., which is not limited here.
[0118] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments. The embodiments can be appropriately modified within the scope of the unchanged main rights.
[0119] Test method:
[0120] (1) Particle size test: The particle size D50 of the positive electrode material is measured using a laser particle size analyzer (Mastersizer 3000), that is, the particle size D50 of the secondary particles of the positive electrode material is measured.
[0121] (2) Tap density (TD) test: Using BT-303 equipment, a certain mass of powder sample is placed in a sample tube and a certain amount of pressure is generated by vibrating the sample tube up and down. After vibrating the sample tube for a period of time, the ratio of the sample mass to the volume after tapping is the tap density.
[0122] (3) Specific surface area test: The specific surface area analysis test method of nitrogen adsorption is used for testing, and the specific surface area analysis test is calculated by the BET (Brunauer Emmett Teller) method. The specific surface area analysis test of nitrogen adsorption can be performed by a Tri Star II specific surface and pore analyzer produced by Micromeritics, USA.
[0123] (4) SEM test: Use a field emission scanning electron microscope to quickly obtain photos of the material surface morphology, such as the Japanese Hitachi Regulus 8100 cold field emission scanning electron microscope.
[0124] (5) SEM section:
[0125] The positive electrode material particles were processed by ion milling to form the cross section of the positive electrode material particles. The acceleration voltage was 6KV, the discharge voltage was 1.5KV, and the air flow size was 0.1cm 3 / min, processing time is 50min.
[0126] A cross-sectional SEM image of the positive electrode material particles at a magnification of 5k is obtained using a field emission scanning electron microscope, and the SEM cross-sectional image is marked by Imagej software, and the average total number of primary particles in a plurality of secondary particles is counted as n0, the average value of the longest diameter of the primary particles in a plurality of secondary particles is the average particle size of the primary particles, and the average number of primary particles ≥1 μm in the plurality of secondary particles accounts for L% of the total number of primary particles. For example, in one embodiment, in the cross-sectional SEM image at a magnification of 5k, n secondary particles are selected, and the total number of primary particles in the n secondary particles is counted as n, respectively. 01 、n 02 、n 03 ……n 0n , n 01 、n 02 、n 03 ……n 0n The sum is calculated and the average value is taken to obtain the average value n0 of the total number of primary particles in the secondary particles. The number of primary particles larger than ≥1 μm in each secondary particle is counted as n 11 、n 12 、n 13 ……n 1n , n 11 、n 12 、n 13 ……n 1n The sum and average are used to obtain the average number n1 of primary particles ≥1 μm in the secondary particles; n1 / n0 is the average number of primary particles ≥1 μm in the secondary particles, n≥5. It should be noted that the radial size of the primary particles in this application refers to the longest diameter of the primary particles.
[0127] Porosity test at the cross section: Use Imagej software to measure multiple secondary particles in the cross-section SEM image to obtain the ratio of the area of the pores in each secondary particle to the area of the cross section of the secondary particle. The average value P% is obtained by summing and averaging the ratios of the areas occupied by the pores in each secondary particle.
[0128] (6) Test on the mass percentage of residual alkali on the surface of positive electrode material:
[0129] The potentiometric titration method is used to read the content. 5 g of powder sample is taken, washed with pure water, and then hydrochloric acid solution is added to the filtrate. The potential change curve is read using an automatic potentiometric titrator. The residual alkali content in the sample is calculated based on the peak position of the curve and the amount of hydrochloric acid standard titration solution consumed.
[0130] (7) Main element and doping element analysis test: ICP was used to test the content of various metal elements in the positive electrode material. The element content in the material was analyzed using an Agilent 5800 ICP spectrometer. The specific operation steps were as follows: 0.4 g of ternary positive electrode material was added to a conical flask, and then 60 mL of pure water and 8 mL of aqua regia were added. The flask was placed on a graphite heating platform and digested at 375 ° C until it was clear. The resulting solution was diluted to 100 mL using a volumetric flask and sampled for dilution. The diluted solution was then analyzed for composition.
[0131] (8) Oil absorption value P test: Use ASAHI S-500 oil absorption value tester equipment, put a certain mass of positive electrode material powder sample into the mixing chamber, then drip linseed oil on the sample at a constant speed to form a semi-plastic agglomerate, and stir it simultaneously with two motor-driven rotating wings; the viscosity of the mixture gradually increases and a peak value appears; the measurement endpoint is the amount of linseed oil dripped when the torque generated by the change in viscosity characteristics reaches the set value or reaches a constant percentage of the maximum torque obtained from the torque curve, and the oil absorption value P (mL / 100g) of the sample to linseed oil is calculated.
[0132] (9) Powder conductivity test: Use a resistivity tester (Suzhou Jingge Electronics ST-2255A), take 5g of positive electrode material powder sample, use an electronic press to press it to 5000kg±2kg, maintain it for 15-25s, and place the sample between the electrodes of the tester. The sample height is h (cm), the voltage at both ends is U, the current is I, and the resistance is R (KΩ). The area of the powder after pressing is S=3.14cM2. The powder electronic conductivity is calculated according to the formula δ=h / (S*R) / 1000, and the unit is S / m.
[0133] (10) Test of lithium ion diffusion rate: The constant current intermittent titration method (GITT) is used to apply a constant current to the system at certain time intervals. During the current pulse, the change in the potential between the working electrode and the reference electrode over time is measured.
[0134] (11) Button battery charge and discharge test: The positive electrode material was mixed with the conductive agent and the binder in a mass ratio of 93:5:2, and NMP was added to the mixture and dispersed in a high-speed disperser for 20 minutes to make a slurry, which was evenly coated on the aluminum sheet. After drying and pressing, the positive electrode sheet was made; the metal lithium sheet was used as the negative electrode to assemble the 2032 battery. The charge and discharge test was conducted using the Blue Electric Test System C001A, with a voltage range of 2.5-4.3V and an ambient temperature of 45°C.
[0135] ①Stand still for 120min; ②Charge at 0.1C to 4.3V, and charge at 4.3V constant voltage to 0.05C to obtain the first charge specific capacity C1; ③Stand still for 3min; ④Discharge at 0.1C to 2.5V to obtain the first discharge specific capacity C2; First coulomb efficiency = C1 / C2.
[0136] The specific test process of 0.5C: After the 0.1C discharge is completed, stand for 3 minutes; ② 0.5C charge to 4.3V, 4.3V constant voltage charge to 0.05C end, and get 0.5C charge capacity C3; ③ Stand for 3 minutes; ④ 0.5C discharge to 2.5V to get 0.5C discharge capacity C4;
[0137] The specific test process of 1C: After the 0.5C discharge is completed, stand for 3 minutes; ② 1C charge to 4.3V, 4.3V constant voltage charge to 0.05C end, and get 1C charge capacity C5; ③ Stand for 3 minutes; ④ 1C discharge to 2.5V to get 1C discharge capacity C6;
[0138] The specific test process of 2C: After the 1C discharge is completed, stand for 3 minutes; ② 2C charge to 4.3V, 4.3V constant voltage charge to 0.05C, and the first charge capacity C7 is obtained; ③ Stand for 3 minutes; ④ 2C discharge to 2.5V to obtain the 2C discharge capacity C8;
[0139] The specific test process of the 50-cycle capacity retention rate is as follows: ② After the 2C discharge is completed, stand for 3 minutes; ② Charge at 1C to 4.3V, and charge at 4.3V constant voltage to 0.05C to obtain the calculated first-cycle specific capacity C9; ③ Stand for 3 minutes; ④ Discharge at 1C to 2.5V to obtain the first-cycle discharge specific capacity C10, and then cycle again for 49 cycles with this 1C charge and discharge process, and the last cycle charging capacity is C11, the last cycle discharge capacity is C12, and the 50-cycle capacity retention rate = C12 / C9*100%.
[0140] Example 1
[0141] (1) 0.9 Co 0.06 Mn 0.04 ](OH)2 and LiOH·H2O, additive ZrO2 and pore-forming agent Li2SO4 are fully mixed in a 10L high mixer at a speed of 1200r / min in a molar ratio of 1:1.04:0.0025:0.001 to obtain a first mixture; the first mixture is subjected to a primary sintering treatment in an oxygen atmosphere, the heating rate of the primary sintering treatment is 2℃ / min, the temperature of the primary sintering treatment is 730℃, the constant temperature time is 10h, and after cooling, it is crushed and sieved to obtain a primary sintering product.
[0142] 2) The primary sintered product and CoOOH are mixed in a molar ratio of 1:0.001 in a 10L high mixer at a speed of 1200r / min to obtain a second mixture; the second mixture is subjected to a secondary sintering treatment in an oxygen atmosphere, the heating rate of the secondary sintering treatment is 2°C / min, the temperature of the secondary sintering treatment is 650°C, the constant temperature time is 5h, and after cooling, it is crushed and sieved to obtain a secondary sintered product.
[0143] 3) The secondary sintered product was mixed with 20° C. pure water in a reaction kettle at a mass ratio of 1:1 for 10 min and demagnetized, and then filtered, side-blown, and dried in a vacuum oven at 170° C. for 24 h to obtain a dried product.
[0144] 4) The dried product and the additive H3BO3 are fully mixed in a 10L high mixer at a molar ratio of 1:0.0005 at a speed of 1200r / min to obtain a third mixture; the third mixture is sintered three times in an oxygen atmosphere, the heating rate of the three sintering treatments is 2°C / min, the temperature of the three sintering treatments is 300°C, the constant temperature time is 5h, and after cooling, it is crushed and sieved to obtain a positive electrode material.
[0145] The positive electrode material prepared in Example 1 includes secondary particles formed by agglomeration of multiple primary particles; a SEM cross-sectional image of the secondary particles is measured at a magnification of 5K by a scanning electron microscope. Figure 2 This is a cross-sectional SEM image of the positive electrode material prepared in Example 1 of the present application. Figure 3 This is a diagram showing the size and number of primary particles in the cross-sectional SEM image of the positive electrode material prepared in Example 1 of the present application. Figure 4 This is a porosity area ratio diagram in the cross-sectional SEM image of the positive electrode material prepared in Example 1 of the present application. Figure 2 to Figure 4 As shown, the number of primary particles with radial size ≥1 μm accounts for 60.5% of all particles, the area of pores in the SEM section image of the secondary particles accounts for 20.6%, and P / L=0.341.
[0146] Example 2
[0147] Compared with Example 1, except step 1) [Ni 0.9 Co 0.06 Mn 0.04 The ratio of ](OH)2 to LiOH·H2O, additive ZrO2 and pore-forming agent Li2SO4 is 1:1.03:0.0025:0.001, and the rest is the same as Example 1.
[0148] Example 3
[0149] Compared with Example 1, except step 1) [Ni 0.9 Co 0.06 Mn 0.04 The ratio of ](OH)2 to LiOH·H2O, additive ZrO2 and pore-forming agent Li2SO4 is 1:1.02:0.0025:0.001, and the rest is the same as Example 1.
[0150] Example 4
[0151] Compared with Example 1, except step 1) [Ni 0.9 Co 0.06 Mn 0.04 The ratio of ](OH)2 to LiOH·H2O, additive ZrO2 and pore-forming agent Li2SO4 is 1:1.05:0.0025:0.001, and the rest is the same as Example 1.
[0152] Example 5
[0153] Compared with Example 1, except step 1) [Ni 0.9 Co 0.06 Mn 0.04 The ratio of ](OH)2 to LiOH·H2O, additive ZrO2 and pore-forming agent Li2SO4 is 1:1.05:0.0025:0.002, and the rest is the same as Example 1.
[0154] Example 6
[0155] Compared with Example 1, except step 1) [Ni 0.9 Co 0.06 Mn 0.04 The ratio of ](OH)2 to LiOH·H2O, additive ZrO2 and pore-forming agent Li2SO4 is 1:1.04:0.0025:0.0015, and the rest is the same as Example 1.
[0156] Example 7
[0157] Compared with Example 1, except step 1) [Ni 0.9 Co 0.06 Mn 0.04 The ratio of ](OH)2 to LiOH·H2O, additive ZrO2 and pore-forming agent Li2SO4 is 1:1.04:0.0025:0.0005, and the rest is the same as Example 1.
[0158] Example 8
[0159] Compared with Example 1, except for changing the primary sintering temperature in step 1) to 750° C., the rest is the same as Example 1.
[0160] Example 9
[0161] Compared with Example 1, except for changing the primary sintering temperature in step 1) to 740° C., the rest is the same as Example 1.
[0162] Example 10
[0163] Compared with Example 1, except for changing the primary sintering temperature in step 1) to 720° C., the rest is the same as Example 1.
[0164] Embodiment 11
[0165] Compared with Example 1, except for changing the heating rate of the first sintering process in step 1) to 1°C / min, the rest is the same as Example 1.
[0166] Example 12
[0167] Compared with Example 1, except for changing the heating rate of the first sintering process in step 1) to 3°C / min, the rest is the same as Example 1.
[0168] Embodiment 13
[0169] Compared with Example 1, except for changing the mass ratio of the secondary sintered product to 20° C. pure water in step 3) to 1:0.6, the rest is the same as Example 1.
[0170] Embodiment 14
[0171] Compared with Example 1, except for changing the mass ratio of the secondary sintering product to 20° C. pure water in step 3) to 1:1.5, the rest is the same as Example 1.
[0172] Embodiment 15
[0173] Compared with Example 1, except for changing the mass ratio of the secondary sintered product to 20° C. pure water in step 3) to 1:2, the rest is the same as Example 1.
[0174] Example 16
[0175] Compared with Example 1, except for changing the mass ratio of the secondary sintering product to 20° C. pure water in step 3) to 1:2.5, the rest is the same as Example 1.
[0176] Embodiment 17
[0177] Compared with Example 1, except for changing the mass ratio of the secondary sintered product to 20° C. pure water in step 3) to 1:4, the rest is the same as Example 1.
[0178] Embodiment 18
[0179] Compared with Example 1, except changing step 1) [Ni 0.9 Co 0.06 Mn 0.04 ](OH)2 is changed to [Ni 0.83 Co0.11 Mn 0.06 ](OH)2, and the rest is the same as in Example 1.
[0180] Embodiment 19
[0181] Compared with Example 1, except changing step 1) [Ni 0.9 Co 0.06 Mn 0.04 ](OH)2 is changed to [Ni 0.88 Co 0.09 Mn 0.03 ](OH)2, and the rest is the same as in Example 1.
[0182] Embodiment 20
[0183] Compared with Example 1, except changing step 1) [Ni 0.9 Co 0.06 Mn 0.04 ](OH)2 is changed to [Ni 0.9 Co 0.5 Mn 0.5 ](OH)2, and the rest is the same as in Example 1.
[0184] Embodiment 21
[0185] Compared with Example 1, except for changing step 1) LiOH·H2O to Li2CO3, the rest is the same as Example 1.
[0186] Embodiment 22
[0187] Compared with Example 1, except changing step 1) [Ni 0.9 Co 0.06 Mn 0.04 ](OH)2 is changed to [Ni 0.9 Co 0.06 Al 0.04 ](OH)2, and the rest is the same as in Example 1.
[0188] Comparative Example 1
[0189] Compared with Example 1, except for changing the molar ratio of the precursor to the lithium salt, the additive T, and the pore former Q in step 1) to 1:1.040:0.0025:0.004, the rest is the same as Example 1;
[0190] Comparative Example 2
[0191] Compared with Example 1, except for changing the molar ratio of the precursor to the lithium salt and the additive T in step 1) to 1:1.060:0.0025, the rest is the same as Example 1;
[0192] Comparative Example 3
[0193] Compared with Example 1, except for changing the temperature of the first sintering treatment in step 1) to 680° C., the rest is the same as Example 1.
[0194] The performance test of the embodiment and the comparative example was carried out, and the test results are shown in Table 1 and Table 3:
[0195] Table 1. Physical and chemical properties of cathode materials
[0196]
[0197]
[0198] Table 2. Physical and chemical properties of positive electrode materials
[0199]
[0200]
[0201] Table 3. Charge and discharge performance of positive electrode materials
[0202]
[0203]
[0204] Combined with the results in Tables 1 to 3, it can be seen from the results of Examples 1-22 that the average total number of primary particles in the secondary particles of the positive electrode material protected by the present application is between 130 and 190; the number of primary particles with a radial size ≥1 μm at the cross section of the secondary particles accounts for 50%-70%, and the number of primary particles ≥1 μm in the secondary particles meets the above range, so that the stress generated by the positive electrode material during the cycle can be well released in the radial direction of the secondary particles, which is beneficial to maintain the integrity of the secondary particles and improve the safety performance of the positive electrode material; at the same time, the secondary particles contain 30%-50% nano-scale primary particles (below 1 μm), and the nano-scale primary particles have a small radial size, which can improve the diffusion rate of lithium ions in the positive electrode material during the charge and discharge process, so that the rate performance and cycle performance of the positive electrode material are improved. Through the synergistic effect of micron-scale particles and nano-scale particles, and controlling the pore area ratio P, the secondary particles can have suitable pores, and the right amount of pores can allow the particles to have a certain space to buffer the stress generated during the cycle. Therefore, in the present application, reasonable porosity and the proportion of the number of micron-sized particles produce a synergistic effect, which can improve the lithium ion diffusion performance of the material, improve the ability to release stress generated during long cycles in a timely manner, reduce the generation of microcracks and the appearance of grain boundaries caused by particle expansion, thereby reducing side reactions and impedance, and the positive electrode material has excellent rate performance, cycle performance and safety performance.
[0205] According to the test data of Comparative Example 1 and Example 1, it can be seen that the pore-forming agent added in the preparation process of Comparative Example 1 is more than that in Example 1, resulting in a significant increase in the proportion of pore area in the positive electrode material, a corresponding increase in the value of P, a decrease in the tap density of the obtained positive electrode material, and a small proportion L of the number of micron-sized primary particles. Under the dual influence of the increase in pores, the cycle retention rate of the positive electrode material is significantly reduced.
[0206] According to the test data of Comparative Example 2 and Example 1, it can be known that in the preparation process of Comparative Example 2, too much lithium salt is added, which leads to increased fusion between some primary particles, and the number of primary particles larger than 1 μm accounts for too large a proportion, that is, the L value is too large, and no pore-forming agent is added in Comparative Example 2, and the P value of the pore area ratio in the positive electrode material particles is also greatly reduced. The density of the positive electrode material is too high, the ion transmission channels are reduced, the lithium ion diffusion rate of the positive electrode material will be greatly reduced, and the rate performance is reduced. At the same time, due to the high density of the positive electrode material, the expansion stress of the positive electrode material is difficult to be effectively released, and the cycle retention rate of the positive electrode material is significantly reduced.
[0207] According to the test data of Comparative Example 3 and Example 1, the primary sintering temperature is too low and the growth of primary particles is restricted, resulting in a decrease in the proportion of primary particles larger than 1 μm and a high proportion of nano-scale particles smaller than 1 μm. As a result, the stress generated during the long cycle of the positive electrode material cannot be released, resulting in a decrease in the cycle capacity retention rate.
[0208] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A positive electrode material, characterized in that: The positive electrode material includes secondary particles, and the secondary particles include a plurality of primary particles; The SEM cross-sectional image of the secondary particles was measured by a scanning electron microscope at a magnification of 5K. In the SEM cross-sectional image of the secondary particles, the average number of primary particles with a radial size ≥1 μm accounted for L%, the average area of the pores accounted for P%, 50≤L≤70, 17≤P≤23.
2. The positive electrode material according to claim 1, characterized in that The positive electrode material satisfies 0.3≤P / L≤0.
4.
3. The positive electrode material according to claim 1, characterized in that In the SEM cross-sectional image of the secondary particles, the number of primary particles with a radial size ≥1 μm is n1, and the total number of primary particles is n0, wherein 130≤n0≤190, 70≤n1≤120; and / or, the average particle size of the primary particles is 0.5 μm to 4 μm.
4. The positive electrode material according to claim 1, characterized in that The chemical formula of the positive electrode material is Li n Ni x Co y M z T e O2, wherein 0.95≤n≤1.6, 0.8≤x<1, 0<y+z≤0.2, x+y+z+e=1, 0≤e≤0.003, wherein the M element is Mn and / or Al, and the T element is a metal element and / or a non-metal element.
5. The positive electrode material according to claim 4, characterized in that It meets at least one of the following technical features: (1) The T element includes at least one of Al, Mg, Sr, Ca, Ti, La, W, Nb, Y, Gd, B, P, and N; (2) The mass percentage content of the T element in the positive electrode material is 0 to 3000 ppm.
6. The positive electrode material according to claim 1, characterized in that The positive electrode material is measured by XRD ray, and the half-peak width of the 003 diffraction peak of the positive electrode material is 0.127-0.174, and the peak intensity ratio of the 003 diffraction peak to the 104 diffraction peak of the positive electrode material is I 003 / I 104 It is 1.6 to 1.
8.
7. The positive electrode material according to claim 1, characterized in that The positive electrode material further includes a coating located on at least part of the surface of the secondary particles, wherein the coating is Li m T a O b , 0≤m<0.5,0 <a<0.002,0<b≤2。 8. The positive electrode material according to any one of claims 1 to 6, characterized in that The positive electrode material satisfies at least one of the following characteristics: (1) The specific surface area of the positive electrode material is 0.32 m 2 / g~0.74m 2 / g; (2) The tap density of the positive electrode material is 2.2 g / cm 3 ~2.9g / cm 3 ; (3) The volume distribution median particle size D50 of the positive electrode material is 8 μm to 13 μm.
9. The positive electrode material according to any one of claims 1 to 6, characterized in that The positive electrode material satisfies at least one of the following characteristics: (1) The powder conductivity of the positive electrode material under a pressure of 20 MPa is 0.002 S / cm to 0.03 S / cm; (2) The lithium ion diffusion rate of the positive electrode material is D cm 2 / s, 10 -12 ≤D≤10 -8 ; (3) The oil absorption value of the positive electrode material is Q mL / 100 g, 12≤Q≤18; (4) The mass percentage of residual alkali on the surface of the positive electrode material is 0.04wt% to 0.16wt%.
10. A battery, characterized in that: The battery comprises the positive electrode material according to any one of claims 1 to 9.
Citation Information
Cited By
Positive electrode active material for all-solid-state battery, preparation method of positive electrode active material, composite positive electrode material for all-solid-state battery and all-solid-state battery
CN120878833A